Blockade of connexin43-containing hemichannel attenuates the LPS-induced inflammatory response in human dental pulp cells by inhibiting the extracellular flux of ATP and HMGB1 - Peiling Hu; Ping Long; Ruotong Li; Xiaorong Lan; Xiaorong Lan; Yuanpei He; Guangwen Li; Guangwen Li; Shiting Li (Frontiers Media S.A., 2024)
IntroductionTissue repair can be promoted by moderate inflammation but suppressed by excessive levels. Therefore, control of excessive inflammation following removal of infection plays a critical role in promotion of pulpal repair. Connexin 43 (Cx43) forms hemichannels (HCs) or gap channels (GJs) to facilitate the delivery of small molecules between cells to regulate both inflammation and repair. Understanding the role of Cx43 in dental pulp may help develop a potential strategy to attenuate the inflammation and promote the formation of reparative dentin in deep caries.MethodsWe firstly investigated the expression profile of Cx43 in infected human third molars by histological analysis; then, we detected channel activity of Cx43 and the effect of mediating release of small molecules in lipopolysaccharide (LPS)-induced inflammation in human dental pulp cells (hDPCs) by molecular biology methods. Results were analyzed by one-way ANOVA and the unpaired t-test. The level of significance was set at α = 0.05.ResultsAnalysis showed that the expression of Cx43 was upregulated in human third molars as the degree of infection increased, and Cx43 was not only expressed in odontoblast layer, but also detected in cell-rich zone and pulp proper. LPS activated Cx43 HCs in hDPCs while inhibiting GJs; blockade of Cx43 HCs attenuated LPS-induced inflammation. Furthermore, LPS promoted the extracellular release of adenosine triphosphate (ATP) and high-mobility group box 1 (HMGB1) within hDPCs, thus exacerbating LPS-induced inflammation. The blockade of Cx43 HCs inhibited the extracellular release of ATP and HMGB1 within hDPCs.ConclusionCollectively, our finding suggested that Cx43 plays a key role in infection and inflammation in dental pulp. LPS activates Cx43 HCs to mediate the extracellular release of ATP and HMGB1 to exacerbate LPS-induced inflammation of hDPCs.